Determination of a gene and environment risk model for age-related macular degeneration. Issue 10 (24th June 2010) - Gibson, Jane; Cree, Angela; Collins, Andrew; Lotery, Andrew; Ennis, Sarah
Abstract : Background/aims: We have recently identified an association between age-related macular degeneration (AMD) and genetic variants in the serpin peptidase inhibitor, clade G, member 1 ( SERPING1 ) gene. In the current study we interrogated the genomic region in linkage disequilibrium (LD) with the SERPING1 gene, and modelled the contribution to disease of known genetic and environmental AMD risk factors. Methods: We analysed genes neighbouring SERPING1 and examined haplotype association with AMD. A stepwise logistic regression model was developed including known genetic and environmental risk factors (age, sex and smoking). Individual risk scores were assessed between groups of cases and controls. Results: In SERPING1 region rs2511989 remains most significantly associated (p=1.77×10 −5, OR 0.67). One haplotype, containing the rs2511989 variant and the majority of SERPING1, exhibits marginally stronger association (p=5.13×10 −6, OR 0.66). Our risk model includes six SNPs in CFH, C3, HTRA1 and SERPING1, showing independent effects, which together account for 45% of risk of developing AMD (p=1.65×10 −50 ) with a combined population attributable risk of 87%. Conclusion: Results implicate SERPING1, with no convincing evidence for involvement of other genes in the region. We demonstrate a multifactorial model with significant differences in risk scores for cases versus controls (p=9.81×10 −71 ) and across Age-Related Eye Disease Study (AREDS) score-stratified cases (p=1.88×10 −11 ).